A combined laser-based angle-resolved photoemission spectroscopy and two-photon photoemission spectroscopy study of Td-WTe2 - Hein, Petra; Jauernik, Stephan; Erk, Hermann; Yang, Lexian; Qi, Yanpeng; Sun, Yan; Felser, Claudia; Bauer, Michael; et al. (Journal of Physics: Condensed Matter, 2020)
Laser-based angle-resolved photoemission spectroscopy and two-photon photoemission spectroscopy are employed to study the valence electronic structure of the Weyl semimetal candidate Td-WTe2 along two high symmetry directions and for binding energies between ≈-1 eV and 5 eV. The experimental data show a good agreement with band structure calculations. Polarization dependent measurements provide further information on initial and intermediate state symmetry properties with respect to the mirror plane of the Td structure of WTe2.
CRIS-Team Scopus Importer:2022-04-14
Keywords: orbital character; polarization-dependent photoemission; selection rules; Two-photon photoemission